How fundamentalism takes root: A simulation study - Daniel Friedman; Jijian Fan; Jonathan Gair; Sriya Iyer; Bartosz Redlicki; Chander Velu (University of California, Economics Department, 2016)
We report agent-based simulations of religiosity dynamics in a spatially dispersed population. Agents' religiosity responds to neighbors via pairwise interactions as well as via club goods effects. A simulation run is deemed fundamentalist if the final distribution contains a sizable minority of very high religiosity together with a majority of lesser religiosity. Such simulations are more prevalent when parameter values shift from values reflecting traditional societies towards values reflecting the modern world. The simulations suggest that the rise of fundamentalism in the modern world is boosted by greater real income, lower relative prices for secular goods, less substitutability between religious and secular goods, and less time spent with neighbors. Surprisingly, the simulations suggest little role for the rise of long distance communication and transportation.
Keywords: Z12; D79; D85; H49; 330; fundamentalism; club goods; agent-based models